PENGARUH KECERDASAN EMOSIONAL TERHADAP PENGGUNAAN MEDIA SOSIAL PADA PESERTA DIDIK - Rohyadi, Kadmyel; Wicaksono, Luhur; Fergina, Ana (Universitas Tanjungpura, 2023)
This study aimed to determine the influence of emotional intelligenceon the use of social media in class IX students at SMP Negeri 22Pontianak. This study used a quantitative approach with descriptivemethod and the form of research used is survey research. Thepopulation in this study was 141 students in class IX, with a totalsample 42 respondents. The collection technique used, namelyindirect communication techniques with questionnaire data collectiontools. Based on the results of the study, it was found that the level ofemotional intelligence possessed by class IX students was 81% in the